Relation texte-image : pratiques d’enseignement dans les situations de lecture d’albums au cycle 3, apprentissages élèves et « schème collectif » - Antonietta Specogna (Recherches en Éducation)
This article is a contribution to the group analysis proposed in this issue. It is based on three studies of 3rd cycle’s cases during children’s literature class with the aim of broaching the connection between text and image, equally in the teaching and in the pupil’s learning process. This theoretical and methodological analysis process comes from psychology and offers an analysis of the teaching activity through the class’ language production. She is based on the practice of teaching and its repercussion on the pupils through collective operatory scheme. By focusing on the visible part of the activity, the regularities and the differences in teaching practices emerging of these three studies are put in evidence. This way, the absence of variations in operatory modes is highlighted.